Draft Genome Sequence of a Novel Bacterium, Pseudomonas sp. Strain MR 02, Capable of Pyomelanin Production, Isolated from the Mahananda River at Siliguri, West Bengal, India - Ranjan, Vivek Kumar (Genome Announc, 2018)
The draft genome sequence of a novel strain, Pseudomonas sp. MR 02, a pyomelanin-producing bacterium isolated from the Mahananda River at Siliguri, West Bengal, India, is reported here. This strain has a genome size of 5.94 Mb, with an overall G+C content of 62.6%. The draft genome reports 5,799 genes (mean gene length, 923 bp), among which 5,503 are protein-coding genes, including the genes required for the catabolism of tyrosine or phenylalanine for the characteristic production of homogentisic acid (HGA). Excess HGA, on excretion, auto-oxidizes and polymerizes to form pyomelanin.